The Rate of S-Element Transformation to Sulfate on Three Kinds of Soils With and Without Addition of Organic Matter - H Muhammad; S Sabiham; A Rachim; H Adijuwana (Jurnal Ilmu Tanah dan Lingkungan, 2005)
Defiency of sulfur were found at many areas of farming in Indonesia. The aim of this experiment was to Icnow the rate ofS-element tranformation to sulfate on three kinds of soil without and added of organic matter. The experiment was conducted using a Randomized Complete Design with factorial pattern consist of two factors and two replications. The first factor is kinds of soil, i.e. Udic Haplusters, Typic Haplustepts, and Oxyaquic Udipsamment. The second factor is dosage of S-element consist offive levels i.e. 20, 40, 60, 80, and 100 mg kg"'. Experiment was arranged in two groups, i.e. without and added 1% of organic matter treatment. Sulfate of each treatment was extracted every ten days by Ca(H]PO.J] content of 500 mg kg"' Pand measured by spectrophotometer on A 432 nm. The result showed that the rate of transformation of S-element to sulfate is significantly affected by kind of soil, S-element dosage, and their interaction. That transformation was on the increase by increasing of time incubation, but the oxidized S persentage was on decrease with an increase of S-element dosage. Addition of organic matter accelerated ransformation of S-element to sulfate on the first stage and decreased with an increase of time incubation.